“I felt like a freak when I would go to the doctor”: Investigating healthcare experiences across the lifespan among older LGBT and transgender/gender diverse adults - Roni Diamant-Wilson; Meagan Ray-Novak; Braveheart Gillani; Dana M. Prince; Laura J. Mintz; Scott Emory Moore (Qualitative Research in Medicine & Healthcare)
In the past several decades, the United States has enacted civil rights legislation protecting lesbian, gay, bisexual, transgender, and queer (LGBTQ) populations from discrimination, including enacting proactive healthcare laws such as the Affordable Care Act. However, given today’s divisive politics, LGBTQ people’s access to appropriate and respectful health care is precarious. This study explored the disconnections from and connections to health care and the respective health effects among two self-identified groups: i) older LGBT adults and ii) transgender and gender-diverse (TG/GD) adults. Using a life course perspective, qualitative data from 17 older LGBT and TG/GD participants were analyzed. Thematic and content analyses indicated that despite progress made, discrimination and prejudice in obtaining health care persist, particularly among TG/GD people of color. The results highlight the ongoing challenges LGBTQ populations face as they risk being denied care by healthcare providers and disconnected from the healthcare system.